Strategic Planning of Information Systems by the application of electronic readiness evaluation (Case Study: An Iranian Pharmaceutical Company) - Mohammadi, Mohadeseh; Ebrahimi Yazdi, Mohammad Mahdi (Nexo Revista Científica, 2022)
The current review considers the assessment of electronic status as one stage of the essential arranging procedure of data frameworks. By concentrating on the current circumstance of the association regarding electronic preparation and distinguishing its qualities and shortcomings, or computerized partition, the essential arrangement of the association's data frameworks can be offered with the goal that the undertakings of data frameworks lead to both the improvement of the advanced gap and acknowledgment of association's systems. Having the data on electronic availability forestalls characterizing those undertakings in the essential arrangement of data frameworks whose requirements are not yet prepared in the association. It assists with building up a solid arrangement for creating Information Technology (IT) depending on the abilities and capacities of the association in various parts of IT.